2016
DOI: 10.14203/oldi.2016.v1i3.55
|View full text |Cite
|
Sign up to set email alerts
|

Gastropoda Mangrove dari Pulau Lombok, Nusa Tenggara Barat

Abstract: <strong>Mangrove Gastropods from Lombok Island, West Nusa Tenggara.</strong> Mangrove forest in Lombok island covers an area of 3,305 ha; an area of 1,643 ha (49.7%) is still in good condition and the remaining 1,662 ha (50.3%) is in damaged condition. The damaged mangrove will impact on the decline of fauna biodiversity. This research was conducted in April 2015 and aimed to determine the composition and distribution of mangrove mollusks, especially gastropods, in Lombok Island. The method used is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 0 publications
0
6
0
15
Order By: Relevance
“…Piranto et al (2019) also found that the high diversity of mangrove species and substrates in Pramuka Island, Jakarta Bay affected the diversity of mollusks, especially species from the Gastropoda class. In mangrove ecosystem in Lombok Island, Mujiono (2016) stated that the highest species diversity was found in the seaward zone. The geographical factor of mangrove forests of the seaward zone located on the coast allows gastropod species from the sea to enter, either intentionally to find food or because they are carried away by waves.…”
Section: Diversity Of Mollusksmentioning
confidence: 99%
“…Piranto et al (2019) also found that the high diversity of mangrove species and substrates in Pramuka Island, Jakarta Bay affected the diversity of mollusks, especially species from the Gastropoda class. In mangrove ecosystem in Lombok Island, Mujiono (2016) stated that the highest species diversity was found in the seaward zone. The geographical factor of mangrove forests of the seaward zone located on the coast allows gastropod species from the sea to enter, either intentionally to find food or because they are carried away by waves.…”
Section: Diversity Of Mollusksmentioning
confidence: 99%
“…Kerusakan hutan mangrove merupakan masalah serius yang kini sedang terjadi hampir di seluruh Indonesia, termasuk di pulau Lombok. Mujiono (2016) memenyatakan kawasan hutan mangrove Pulau Lombok yang masih dalam kondisi baik hanya sekitar 1.643 ha atau sekitar 49,7% dari total 3.305 ha kawasan hutan mangrove Pulau Lombok. Sebagai upaya mengurangi laju kerusakan hutan mangrove, maka dilakukannlah rehabilitasi ekosistem mangrove.…”
Section: Pendahuluanunclassified
“…Jika dilihat dari fauna asosiasi mangrove yang ditemukan di kedua lokasi penelitian, keanekaragaman jenis fauna di ekosistem mangrove alami Pemongkong jauh lebih tinggi dibandingkan dengan ekosistem rehabilitasi Gerupuk. Terdapat 34 spesies moluska asosiasi seperti Cherithidea spp., Littorina spp., dan sebagainya (Zvonareva et al, 2015;Mujiono, 2016;Yolanda, 2016)…”
Section: Keterangan; Iss: Indeks Similiaritas Sorensen; Psunclassified
“…Note: *stored in MZB, # type locality from Lombok, nr (new record), FW (freshwater), MG (mangrove), MR (marine), TR (terrestrial). (Mujiono, 2016). The other five Littoraria species are probably have a similar preference.…”
Section: Resultsmentioning
confidence: 96%
“…The other five Littoraria species are probably have a similar preference. Chicoreus is the only one genus of Muricidae that specialized to hunt their prey in mangrove (Tan, 2008;Mujiono, 2016). However, they also frequently found in open marine water (Rahmasari et al, 2015).…”
Section: Resultsmentioning
confidence: 99%